1976
DOI: 10.1042/bj1580109
|View full text |Cite
|
Sign up to set email alerts
|

Induction of benzo[a]pyrene Mono-oxygenase in liver cell culture by the photochemical generation of active oxygen species. Evidence for the involvement of singlet oxygen and the formation of a stable inducing intermediate

Abstract: 1. The photochemical generation of excited states of oxygen in liver cell culture by the mild ilumination of culture medium containing riboflavin, results in stimulation of benzo[a]pyrene 3-mono-oxygenase, a cytochrome P-450-linked mono-oxygenase. 2. The same large increase in mono-oxygenase activity was found when medium containing riboflavin was illuminated in the absence of cells and then stored in the dark for 24h before contact with the cells. From this it may be inferred that stimulation is due to the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Furthermore, the present investigation offers a relatively straightforward explanation for the reported ability of numerous structurally diverse chemicals to activate the AHR; such reports have been used to argue that the AHR binds ligands promiscuously (37). Our results also may explain why the addition of fresh Trp-containing medium to cell cultures (42), oxidative stress [e.g., by hyperoxia (43)], and hydrodynamic shear that gives rise to oxidized LDL (44,45), as well as why the addition of various complex mixtures, such as extracts of paper and ink, can activate the AHR (46,47).…”
Section: Discussionsupporting
confidence: 57%
“…Furthermore, the present investigation offers a relatively straightforward explanation for the reported ability of numerous structurally diverse chemicals to activate the AHR; such reports have been used to argue that the AHR binds ligands promiscuously (37). Our results also may explain why the addition of fresh Trp-containing medium to cell cultures (42), oxidative stress [e.g., by hyperoxia (43)], and hydrodynamic shear that gives rise to oxidized LDL (44,45), as well as why the addition of various complex mixtures, such as extracts of paper and ink, can activate the AHR (46,47).…”
Section: Discussionsupporting
confidence: 57%
“…In vitro and in vivo studies have shown that the byproducts of tryptophan photooxidation possess a high AhR-binding capacity and are able to induce the expression of Cyp1a1 and other AhR target genes. [61][62][63][64] A prime example of a tryptophan photoproduct is a 6formylindolo[3,2-b]carbazole (FICZ), which displays a significant structural similarity and potency to ICZ and can agonistically stimulate AhR activity in as low as picomolar ranges [65][66][67] (Fig. 2).…”
Section: Indole and Tryptophan Metabolitesmentioning
confidence: 99%
“…S1C,D), indicating that there was not a general effect on nucleocytoplasmic shuttling arising from UV exposure. Light-activated AHR signaling has been observed in a variety of cultured cells since the first report by Paine in 1976 24 , and the functional relevance of tryptophan as an UVB chromophore for formation of an endogenous AHR-activating photoproduct that explains the effect of light on cells has been repeatedly documented 13,2528 .
Figure 1UVB induces AHR translocation to the nucleus and the expression of its target genes, in vitro . ( A ) Western Blot analyses of AHR from nuclear and cytoplasmic fractions from SCC25 cells 1 hr following irradiation with 15 min UVB.
…”
Section: Resultsmentioning
confidence: 97%